Rapid characterization of emulsions by pulsed field gradient nuclear magnetic resonance - Sørland, Geir Humborstad; Keleşoğlu, Serkan; Simon, Sébastien; Sjöblom, Johan (Diffusion Fundamentals, 2013)
A method for rapid characterization of emulsions is presented. From the proposed setup we are able to measure the droplet size distribution of brine or water droplets confined by an oil phase, even though there is complete overlap in relaxation times and/or molecular mobility between the water and the oil phases. A PFG-NMR sequence is presented that applies the spoiler recovery method for significant reduction in acquisition time, and the method is used for rapid characterization of emulsions.